Head to head: should we adopt the term 'sessile serrated lesion'?. Issue 7 (3rd March 2022) - Nagtegaal, Iris D; Snover, Dale C
Abstract : The precursor lesion for the ~30% of colon carcinomas developing along the serrated pathway was first described in detail in 1996, and was named sessile serrated adenoma in 2003. Although the entity itself was controversial initially, over time the concept of a serrated pathway initiated by this lesion has become well accepted in the medical community. The name sessile serrated adenoma, however, has been controversial since the beginning and continues to be controversial. Alternative names, including serrated polyp with abnormal proliferation, sessile serrated polyp and, most recently, sessile serrated lesion, have been proposed. Despite the fact that the term sessile serrated lesion was adopted by the World Health Organization in 2019, none of these terms has received universal acceptance. In this article, arguments for and against adopting the term sessile serrated lesion are discussed in detail. Abstract :